Can diffusion and T2 star-weighted magnetic resonance imaging aid in the diagnosis of ectopic endometrium? - Mariam Raafat (The Egyptian Journal of Radiology and Nuclear Medicine, 2021)
Abstract Background Endometriosis is a common gynecologic disorder characterized by the implantation of the endometrial tissue ectopically outside the endometrial cavity. It affects about 10% of females at the childbearing period and is estimated to be present up to 20–50% in women complaining of infertility. While laparoscopy is considered the mainstay for diagnosis, magnetic resonance imaging (MRI) is recognized as a useful tool for definitive diagnosis, pre-surgical planning, and determining whether the patient will require multi-specialty involvement. The aim of this study is to evaluate the performance of MRI with the addition of diffusion-weighted imaging (DWI) and T2 star (T2*) to conventional MRI, for the accurate assessment of ectopic endometrium. Results Endometriotic lesions that showed diffusion restriction on DWI were 80.7%, and 96.1% of the endometriotic lesions had signal voids on the T2*W sequence, whereas only 65.4% of the lesions had typical signal intensities on T1WI and T2WI. Diagnostic performance of the MRI examination was improved by the use of the diffusion sequence and better improved by the T2* sequence, compared to the conventional MR protocol sensitivity (SE) = 96.12% and specificity (SP) = 85.7% in T2*-weighted images, SE = 80.7% and SP = 71.4% in DWI, and SE = 65.4% and SP = 71.4% in conventional MRI. P value for conventional MRI was 0.1, which is of no statistical significance (p < 0.05). P value for DWI was 0.016, which is statistically significant (p < 0.05). P value for T2*WI was 0.001, which is more statistically significant (p < 0.05) and could be adequately correlated with laparoscopy. Conclusion DWI and T2* significantly increase MRI diagnostic accuracy by allowing the detection of the hemorrhagic character of the endometriotic lesions. Studies with a large sample size are needed to confirm that they can replace invasive laparoscopy for the diagnosis of endometriosis.